Dravidian and Altaic ‘to wave / to tremble - arm / shoulder-(blade) / wing’ - Jaroslav Vacek (Acta Mongolica, 2009)
The paper summarizes one complex Dravidian and Altaic etymological nest consisting of a verb meaning to wave / to tremble’, and a body part ’arm / shoulder-(blade)’ wing’. This dynamic etymological nest constitutes a significant addition to the general picture ofthe Dravidian and Altaic parallels - on the one hand it concerns the parallel verbal etyma. on the other the motivated designation:-,. in this case of a body part (cf. Vacek 2007b for a similar case). The paper is to be read in the context of other discussions of the general linguistic aspects and interpretations of the Dravidian and Altaic relationship pioposcd by il.c author (ancient linguistic area/areas, high contact languages; Vacek 2002a, 2004b. and particularly recent papers in press, Vacek 2009, 2010a,b).